PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN PROFESIONALISME TERHADAP KINERJA PEGAWAI DINAS PU BINA MARGA DI KABUPATEN SUMENEP - Woro Utari; Hariwibowo; Tri Andjarwati (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study is determine the effect of motivation, work ability, and professionalism simultaneously and partially has an influence on the performance of the Department of Public Works staff in Sumenep Regency, and To find out among the motivations, work skills, and professionalism that have a dominant influence on the Office of Public Works in Sumenep Regency. The results showed that simultaneously, motivation, work ability, and professionalism had a very significant influence on employee performance, as evidenced by the calculated F value of 1.540 with a significance level of 0.113 (smaller than 0.05). Partially, motivation, work ability, and professionalism have a significant influence on the Department of Public Works in Sumenep Regency. This is evidenced by the t value of each independent variable, namely: the motivation of the t value of 1.635 with a significance level of 0.001, the ability work value of t arithmetic of 0.127 with a significance level of 0.30 and professionalism with a value of t arithmetic of 0.905 with a significance level of 0.002 (less than 0.05). Thus it can be said that all independent variables partially have a significant effect on employee performance at the Department of Public Works in Sumenep Regency; and motivation variables have a very dominant influence in influencing the performance of employees at the Department of Public Works in Sumenep Regency.